Habeas corpus : a very short introduction - Tyler, Amanda L. (New York, NY : Oxford University Press, 2021)
For nearly eight hundred years, the writ of habeas corpus has limited the executive in the Anglo-American legal tradition from imprisoning citizens and subjects with impunity. The writ empowers the judiciary to determine whether an arrest has been made with just cause and, where appropriate, to award prisoners their freedom. For this reason, the eighteenth-century jurist William Blackstone described the writ of habeas corpus as a 'bulwark' of our liberties and the English Habeas Corpus Act of 1679 as a 'second Magna Carta.' Amanda L. Tyler traces the history of habeas corpus from its origins in English law to its spread throughout the world and its incorporation in the American constitutional framework, giving special attention to its application at various flashpoints in recent history, including during World War II and the War on Terror.
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 1, 2021).
Keywords: Habeas corpus -- History; Habeas corpus -- Great Britain; Habeas corpus -- United States -- History